Characterization of high-pressure die-cast hypereutectic Al-Si alloys based on microstructural distribution and fracture morphology. Issue 6 (June 2019) - Jiao, X.Y.; Wang, J.; Liu, C.F.; Guo, Z.P.; Tong, G.D.; Ma, S.L.; Bi, Y.; Zhang, Y.F.; Xiong, S.M.
Abstract: The fracture behavior of high-pressure die-cast hypereutectic (HPDC) Al-Si alloys was investigated using a high-resolution laboratory CT and synchrotron X-ray tomography with a particular focus on the influence of HPDC microstructure. Results showed that microstructure of the alloy was mainly comprised of primary silicon particles (PSPs), Al dendrites, Cu-rich phases and pores. Most of the coarse PSPs, Cu-rich phases and pores were located in the center of the specimen. The rapid solidification of HPDC led to a heterogeneous microstructural feature. Elemental Cu was enriched in the frontiers of solid-liquid interface, causing the formation of large size dendritic arms. The pores were formed in the interdendrites which endured high stress intensity under high applied stress. Microcracks were originated from pores and further connected Cu-rich phases causing intergranular fracture. PSPs worked as obstacles causing piling-up dislocations in the phase interface. In the regions where large size of PSPs enriched in, PSPs ruptured rather than debonded from matrix, indicating transgranular fractures of PSPs. Microcracks originated around pores and PSPs tended to converge on the main cracks to decrease the energy required for crack propagation.